β-Catenin Signaling Evokes Hair Follicle Senescence by Accelerating the Differentiation of Hair Follicle Mesenchymal Progenitors - Han, Jimin; Lin, Kaijun; Choo, Huiqin; He, Jia; Wang, Xusheng; Wu, Yaojiong; Chen, Xiaodong (Frontiers in Cell and Developmental Biology, 2022)
Rationale: β-catenin signaling controls multiple fibroblast subsets, with its overactivity promoting the differentiation of hair follicle dermal stem cells (hfDSCs) and the hyperactivation of interfollicular fibroblasts. Understanding the concept of hfDSC activation and modulation offers hope towards the therapeutic armamentarium in dermatology and related comorbidities, as well as their potential applications in gerontology (the study of physiological aging). Having a comprehensive understanding in this stochastic process could also further yield important, novel insights into the molecular basis of skin aging to improve lifespan and preventing aging-related diseases. Methods: A new CD34CrePGR mouse line was generated. Through fate-tracing models and a series of β-catenin genetic experiments, our study depicts how the wound environment increases phosphorylated β-catenin in hfDSCs and facilitates their differentiation into dermal papilla (DP) and dermal sheath (DS). In mice carrying hfDSC-specific activated allele of β-catenin, hfDSCs accelerated their differentiation into DP cells. Results: Notably, with β-catenin stabilization in CD34-expressing cells and potential activation of canonical Wnt signaling, the mutant mice showed a brief increase of hair density in the short term, but over time leads to a senescence phenotype developing premature canities and thinning [hair follicle (HF) miniaturization]. Conclusion: β-catenin signaling drove HF senescence by accelerating differentiation of CD34+ hfDSCs, resulting in phenotypes attributable to the differentiation of the hfDSCs into DP cells and the loss of their stem cell potential. Therefore, our study reveals that the regulation of β-catenin signaling in hfDSCs may potentially become an important subject for future exploration in development of clinically effective therapies for hair loss treatment and an excellent model for revealing new therapeutic approaches to reverse aging or retarding the development of alopecia.